Penerapan Manajemen K3 Dengan Metode Job Safety Analysis Pada Pemasangan Profile Baja (Studi Kasus Pembangunan Workshop PT. Ultra Sakti) - Ramdan, Muhammad; Putri, Isria Miharti Maherni; Putra, Alfandias Seysna (Universitas Pelita Bangsa, 2024)
Work accidents are a problem that often occurs in various construction projects, including in workshop construction. To overcome this, implementing Occupational Health and Safety (K3) management is very important. This research aims to evaluate the implementation of K3 management with a focus on the use of the Hazard Analysis and Control Method (Job Safety Analysis) in preventing work accidents in workshop construction projects. The research method used is field research with a qualitative approach. Data was collected through direct observation, interviews with workers and project managers, as well as analysis of documents related to K3. The process of implementing JSA is evaluated from the stage of identifying hazards, determining control measures, to implementing preventive measures. The research results show that the implementation of K3 management, especially through the use of the JSA method, has a significant role in reducing the risk of work accidents. Systematic identification of hazards and determination of appropriate control measures and helps increase awareness of potential risks in the workplace. Apart from that, this research makes an important contribution in strengthening understanding of the importance of implementing K3 management in the construction industry, especially in the installation of erections for workshop construction. Recommendations are provided to continue to improve the use of the JSA method and to achieve a safer and more productive work environment.